KEMAMPUAN MENULIS NASKAH DRAMA SISWA KELAS VIII SMP NEGERI 20 PADANG DENGAN MENGGUNAKAN MEDIA CERPEN - Asmawati, Asmawati; Nisja, Indriani; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2014)
This research is motivated by three issues (1) students are less able to describeÂ backround in a play, (2) students are less able to the deter mine a character in a play, and (3) students are less able to describe the sequence of events in a drama scipt by using the media stories. The purpuse ofthis study was to describe the ability to write a play grade VIII SMP N 20 Padang by using the media stories. This type of research is a quantitative study using descriptive methods. This study population is grade VIII SMPN 20 Padang of the school year 2013/2014. Number of students, the population in this study were 236 students, the largest in the eight grade. The study sample was 28 people. Data in this study were obtained by means of giving the test to students. Based on the results of a study of the ability to write a play grade VIII SMPN 20 Padang by using the media stories following condusions can be drawn. The first ability to write a play using media stories for indicator 1 (describing background) are in good qualification (B) with an avarage of 84,52 students second, the indicator 2 (figures are in perfect qualificatin (S) with an avarage of 100 students, and third , indicator 3 (series events) are more enough in qualifying (LDC) with an avarage of 70,23 students. Based on research result that has beenÂ done on the ability to write a play grade SMPN20 Padang by using the media stories can be concluded that the ability to write a play VIII SMPN 20 Padang earned an avarage of 84,93 were the range of 76-85% well qualified (B).Â